2017
DOI: 10.1111/bjso.12216
|View full text |Cite
|
Sign up to set email alerts
|

Low relational mobility leads to greater motivation to understand enemies but not friends and acquaintances

Abstract: Enemyship occurs across societies, but it has not received as much attention as other types of relationships such as friendship in previous research. This research examined the influence of relational mobility on people's motivation to understand their personal enemies by measuring different dependent variables across three studies. First, a crosscultural comparison study found that Hong Kong Chinese, from a low-relational-mobility society, reported a stronger desire to seek proximity to enemies relative to Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
(107 reference statements)
1
18
1
Order By: Relevance
“…First, our findings were based on self-reported cross-sectional data. Specifically, while relational mobility is conceptualized as a socioecological construct, we draw from self-reported measures rather than objective and/or behavioral measures (such as divorce/remarriage rates, job turnover rates, and residential mobility; Li, Masuda, & Lee, 2018). For instance, Li, Masuda, and Lee (2018) employed an experimental manipulation method to investigate a causal relationship between “induced” relational mobility and changes in interpersonal behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our findings were based on self-reported cross-sectional data. Specifically, while relational mobility is conceptualized as a socioecological construct, we draw from self-reported measures rather than objective and/or behavioral measures (such as divorce/remarriage rates, job turnover rates, and residential mobility; Li, Masuda, & Lee, 2018). For instance, Li, Masuda, and Lee (2018) employed an experimental manipulation method to investigate a causal relationship between “induced” relational mobility and changes in interpersonal behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, while relational mobility is conceptualized as a socioecological construct, we draw from self-reported measures rather than objective and/or behavioral measures (such as divorce/remarriage rates, job turnover rates, and residential mobility; Li, Masuda, & Lee, 2018). For instance, Li, Masuda, and Lee (2018) employed an experimental manipulation method to investigate a causal relationship between “induced” relational mobility and changes in interpersonal behaviors. Also, though self-reported health has implications for mortality (McGee, Liao, Cao, & Cooper, 1999), we did not find any significant indirect effects of relational mobility to physical health using the self-reported measure.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships in this type of environment can be fragile; therefore, individuals engage in self‐disclosure to increase the chance that they will be liked by others (Schug et al, 2010). Being adaptive to such socioecology, individuals with high RM possess greater general trust (Thomson, Yuki, & Ito, 2015) and risk‐taking propensity in interpersonal behaviour (Li, Hamamura, & Adams, 2016), and are with less concern with enemies in eye‐tracking tasks (Li, Masuda, & Lee, 2018), relative to those with low RM. Moreover, people in societies with high RM (e.g., Canada) are less sensitive to social rejection, relative to that observed in those in societies with low RM (e.g., Hong Kong; Lou & Li, 2017).…”
Section: A Socioecological Understanding Of the Effect Of Mobility Onmentioning
confidence: 99%
“…It has been shown that the negative influence of PSP was more notable when people failed to pretend to have a perfect image in front of others (Flett & Hewitt, ; McGee et al., ). Culture, which leads to the evolution of different interpersonal strategies (Li, Masuda, & Lee, ; Lou & Li, ; Yuki, Maddux, Brewer, & Takemura, ), can be another potential moderating factor. However, the relationship between culture and different forms of perfectionism has been ignored, which may be especially true for PSP.…”
Section: Pspmentioning
confidence: 99%
“…Interpersonal connection is in the form of dense overlapping networks rooted in a given social context, which in turn encourage the use of defensive (or prevention‐oriented) interpersonal strategies to maintain stable existing social relationships (Li et al., ). For instance, Asians are more likely to be motivated to understand their enemies (Li, Masuda, & Lee, ), save face (M. Chen, ; Wierzbicka, ), and suppress their negative emotions to preserve relationships (Matsumoto, ; Soto, Perez, Kim, Lee, & Minnick, ). Therefore, in Asian social contexts, relational concerns are greater than the need to express one's personal self (Yamagishi et al., ).…”
Section: Pspmentioning
confidence: 99%